Farmer management of groundwater irrigation in Asia: selected papers from a South Asian Regional Workshop on Groundwater Farmer-Managed Irrigation Systems and Sustainable Groundwater Management, Dhaka, Bangladesh 18-21 May 1992 - Abhayaratna, M. D. C.; Vermillion, Douglas L.; Johnson, S.; Perry, C. (International Irrigation Management Institute, 1994)
In this workshop the participants identified five priority areas of concern relative to sustainable management of groundwater irrigation by farmers:1) aquifer drawdown; 2) FMIS groundwaterwater support services, 3) management problems under water-surplus conditions; 4) management problems under water-deficit conditions; 5) management problems in conjunctive use areas .